Production Of Vinyl Esters Based On Vinylation Of Ethanolamine With Acetylene - Juraboev Fozil Mamasolievich; Nurmonov Suvonkul Erkhonovich (Global Scientific Publishing, 2024)
Recently, a lot of scientific work has been carried out to create methods for producing vinyl compounds of substances containing active hydrogen atoms in superbasic systems. In this work, we studied the vinylation of monoethanolamine with acetylene in superbasic media. The effect of temperature, catalyst, reaction time, and other factors on the yield of vinyl ester of monoethanolamine has been studied. Also, quantum-chemical calculations theoretically calculated the active reaction centers of monoethanolamine, the distribution of atomic charges
Keywords: monoethanolamine; vinylation process; vinyl ester; hydroxyl group